Sound Generator Berbasis Superposisi Gelombang Sinus untuk Alat Peraga Praktikum - Tri Agus Djoko Kuntjoro; Dwi Edi Setyawan; Billy Montolalu (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2019)
This paper discusses the sound generator which uses of sine waves superposition to produce musical sounds. The sound generator was then further used as practicum module by electrical engineering students in the electrical physics course. Especially to better understand about electrical waves and its parameters. This sound generator is considered to be a more effective learning tool in comparison to the  oscilloscope and function generators, which are more commonly used. To build the sound generator, a simple and precise architectural design is required. The architecture consist of  microcontroller as main processor and several RC integrators to convert square waves into sine waves. The algorithm in the microcontroller was aranged to produce a harmonious melody. In summary, this paper discusses the complete and comprehensive process of constructing a sound generator including its architectural design, generation process of sine waves, superposition of waves, and also the process of composing a tone scenario in order to produce a harmonious melody.